Talent Management Digitalization Strategy: The Role of AI, Training, and Organizational Culture - Suraining Rosodor; Freddrick Tiagita Putra (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The transformation of student organizations in the digital era faces significant challenges in human resource management, particularly in talent management. Reliance on conventional training methods, a relatively static organizational culture, and the low utilization of technologies such as artificial intelligence (AI) create significant gaps in the development of member potential. This phenomenon demands a more dynamic, adaptive, and technology-based talent management approach to address the complexities of globalization and digitalization. This study aims to analyze the influence of training, organizational culture, and the use of AI on the effectiveness of talent management in student organizations. A quantitative approach with an explanatory design was used in this study, involving 74 respondents purposively selected from 285 student organization members of the Faculty of Economics and Business, University of Islam Malang. Data analysis techniques included multiple linear regression and a series of classical assumption tests. The results showed that all three independent variables significantly influenced talent management, both partially and simultaneously, with an adjusted R² value of 66.9%. This finding presents a novel approach in the integration of AI, particularly through computer vision technology and expert systems, as an efficient and objective data-driven evaluation and decision-making tool. This approach is still rarely implemented in the context of non-formal higher education organizations. The practical implications of this research emphasize the importance of synergy between targeted training, collaborative organizational culture, and technological innovation to strengthen competitiveness, loyalty, and leadership quality in sustainable student organizations.